Problems associated with working of the Palestinian zakat authority during the years (2008-2021) - Elshobake, Mohammed R. M. (Lembaga Zakat Negeri Kedah Darul Aman, 2023)
Zakat is one of the five pillars of Islam, and it is an obligation according to the Qur’an, Sunnah, and consensus "Ijmā". It is also considered a basic financial resource in the Islamic state. Many Islamic countries have taken an interest in the issue of regulating Zakat and have issued laws organizing Zakat. Thus, the Legislative Council in Gaza issued Law No. (9) of 2008 as the first law regulating Zakat in Palestine, but this law was accompanied by many problems that hindered its implementation. Using the inductive and analytical approaches, this research seeks to clarify these problems in order to come up with recommendations that contribute to the application of the law regulating Zakat in all parts of Palestine. This research concluded that there are a number of political, administrative, financial and legal problems that affected the application of the Zakat Law, but efforts to develop the work of the Palestinian Zakat Authority and remove obstacles still exist. This research recommends concerted efforts from all responsible parties in order to implement the Palestinian Zakat Authority law in all parts of Palestine, and to achieve coordination and integration between the Palestinian Zakat Authority and tax collection departments and all relevant institutions, and to overcome all obstacles that hinder the work of the Palestinian Zakat Authority so that this body can perform its role Legal and institutional in an optimal manner.